An Evolution Model of Fintech Supports Technology-Based SMEs Innovation and Growth - Lei Zhuang; Han Zhou; Tingqiang Chen (Discrete Dynamics in Nature and Society)
The survival and growth of technology-based small and medium-sized enterprises are faced with a complex and changeable market environment. Introducing the role of fintech, the paper builds an evolutionary model for growth of technology-based SMEs and analyzes fintech incentive mechanisms to guide corporate growth strategies based on some cases by the simulation. The research results show that the evolutionary game strategy that SMEs are willing to adopt is {cooperation, cooperation}. And, under the incentive mechanism of fintech, the evolutionary game strategy adopted by SMEs and fintech institutions is {cooperation, cooperation, participation}. In the growth of fintech institutions serving technology-based SMEs, the selection strategy of SMEs is more sensitive to changes in fintech institutions’ willingness to participate in cooperation, cooperation costs, and cooperation benefits. The selection strategy of fintech institutions is more affected by changes in cooperation costs and incentive funds during the process of participating in cooperation.